Genome Sequence of Acinetobacter sp. Strain P8-3-8, Isolated from Fistularia commersonii in Vietnam - Kim, Young-Ok (American Society for Microbiology, 2011)
Acinetobacter sp. strain P8-3-8 is an aerobic, Gram-negative marine bacterium isolated from the intestine of the bluespotted cornetfish (Fistularia commersonii). Here, we present the draft genome sequence of Acinetobacter sp. P8-3-8 (3,905,565 bp, with a G+C content of 37.6%) containing 3,621 putative coding sequences. The genome data reveal a high density of genes encoding transcriptional regulators involved in anaerobic respiration.